2020
DOI: 10.1177/2331216520945826
|View full text |Cite
|
Sign up to set email alerts
|

Can You Hear Out the Melody? Testing Musical Scene Perception in Young Normal-Hearing and Older Hearing-Impaired Listeners

Abstract: It is well known that hearing loss compromises auditory scene analysis abilities, as is usually manifested in difficulties of understanding speech in noise. Remarkably little is known about auditory scene analysis of hearing-impaired (HI) listeners when it comes to musical sounds. Specifically, it is unclear to which extent HI listeners are able to hear out a melody or an instrument from a musical mixture. Here, we tested a group of younger normal-hearing (yNH) and older HI (oHI) listeners with moderate hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 77 publications
(104 reference statements)
2
17
0
Order By: Relevance
“…It is to be noted, that our analysis revealed no systematic differences between participants who declared themselves as musician and those who did not. This held true across all three experiments, even though in previous studies, musicians showed improved results in ASA tasks (e.g., Başkent et al, 2018 ; Madsen et al, 2019 ; Siedenburg et al, 2020 ). The most likely reason to explain this may be that we did not specifically control for an equal number of musicians and non-musicians in a large sample; thus, the proportion of participants considered musicians were only a fraction of the total participants, and therefore the sample size may be too small for an adequate statistical comparison.…”
Section: Experiments 1: Unmodified Excerptssupporting
confidence: 66%
See 1 more Smart Citation
“…It is to be noted, that our analysis revealed no systematic differences between participants who declared themselves as musician and those who did not. This held true across all three experiments, even though in previous studies, musicians showed improved results in ASA tasks (e.g., Başkent et al, 2018 ; Madsen et al, 2019 ; Siedenburg et al, 2020 ). The most likely reason to explain this may be that we did not specifically control for an equal number of musicians and non-musicians in a large sample; thus, the proportion of participants considered musicians were only a fraction of the total participants, and therefore the sample size may be too small for an adequate statistical comparison.…”
Section: Experiments 1: Unmodified Excerptssupporting
confidence: 66%
“…Although no clear effect for a modification of timbral dissimilarity could be observed, the results implied a trend that a reduction of timbral dissimilarity and thus a reduction of acoustical cues lead to a deterioration of stream segregation, further suggesting that a minimum of exogenous cues is necessary to track and separate single streams. In Siedenburg et al (2020) , listeners had to hear out instruments and melodies of varying sound level masked by a simultaneously playing instrument. It was found that participants were able to exploit dips in the masker signal, allowing them to hear the target instrument at lower levels than with a masker that did not contain these dips.…”
Section: Introductionmentioning
confidence: 99%
“…In the statistical analysis, adding the musical training index to the model did not improve the model fit. Note that previous studies of scene analysis found that musical training improved performance of participants in several scene analysis tasks (see e.g., Madsen et al, 2019;Siedenburg et al, 2020). In the present study, we did not undertake a dedicated comparison of groups of participants with and without musical training, and our musical training index mainly encoded variations in the degree of musical training.…”
Section: Discussionmentioning
confidence: 78%
“…This project has received funding from the European Union's Framework Programme for Research and Innovation Horizon 2020-2020 under the Marie Skłodowska-Curie Grant Agreement No. 747124.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation